2022
DOI: 10.1097/pts.0000000000001080
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Claims for Wrong-Side, Wrong-Organ, Wrong-Procedure, or Wrong-Person Surgical Errors: A Retrospective Study for 10 Years

Abstract: Objective: Serious adverse events, such as wrong-side, wrong-organ, wrong-procedure, or wrong-person errors, still occur despite the implementation of preventative measures. In France, we describe the claims related to such errors based on the database from one of the main insurance companies.Methods: A retrospective analysis of claims declared between January 2007 and December 2017 to Relyens, a medical liability insurance company (Sham), was performed. Their database was queried using the following keywords:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The value of such a large and well-structured sample containing judicial and extrajudicial cases must be highlighted, which has allowed them to analyze a surprisingly long series of cases. We agree with the authors that this kind of surgical errors is rare but fully preventable by the implementation of a patient safety culture 1 . However, these types of surgical errors, although foreseeable, are present in all health care systems around the world, 2,3 and this fact indicates that, even relatively easy to prevent, we should continue to make efforts in this area.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…The value of such a large and well-structured sample containing judicial and extrajudicial cases must be highlighted, which has allowed them to analyze a surprisingly long series of cases. We agree with the authors that this kind of surgical errors is rare but fully preventable by the implementation of a patient safety culture 1 . However, these types of surgical errors, although foreseeable, are present in all health care systems around the world, 2,3 and this fact indicates that, even relatively easy to prevent, we should continue to make efforts in this area.…”
supporting
confidence: 74%
“…Similarly to the French sample, it collects information from the main physician’s professional liability insurance company in Catalonia (>26,000 physicians insured) and provides medical evidence from research as a rich source of learning from error 5 . We analyzed the same period as the study by Vacheron et al 1 (2007–2017), and we found 43 cases, 39 related to wrong site surgery (including wrong side and wrong organ) and 4 to wrong procedure. Unfortunately, our database does not include recorded cases of wrong person in surgical errors.…”
mentioning
confidence: 99%
See 3 more Smart Citations